If climate change can trigger civil conflict, can good policy trigger peace? Empirical evidence from cross-country panel data - Sherin Khalifa; Svetlana Petri; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
Based on the analysis of a new cross-country panel data from Africa and the Middle East for the time period between 1981 and 2015, we show that reductions in per capita income growth rate or domestic food production induced by climate variation significantly increase the probability of civil conflict. A 10% reduction in economic growth or domestic food production leads to a 1.25% and 1.59% increase in the likelihood of civil conflict, respectively. Furthermore, we identify a direct link of climate on the incidence of civil conflict. Additionally, the level of democracy and good governance are good control variables. Regarding the Syrian conflict, when considering 2010 data, the increase in temperature growth explains around 30% of falling income growth as well as 85% of the shrinking food production index and in this way contributed to the onset of war. We explain the probability of ongoing conflict by 43-56%. The two strongest factors explaining the conflict are lagged conflicts and economic development. Adequate economic policies that are able to accelerate economic development, play a role in peace, and avoiding new conflicts.
urn:nbn:de:gbv:8:3-2021-00200-8
Keywords: 330; Climate variation; economic growth rate; food production index; civil war